The Meaning of Venetian History in Ruskin and Pound - Casillo, Robert (University of Toronto quarterly, 1986)
Although Ezra Pound figures within the aesthetic and economic tradition which Ruskin inaugurated, the paucity of direct references to Ruskin in Pound's work has often discouraged inquiry into their relation. The resemblance between these writers lies not so much in textual affiliations or borrowings or in demonstrable influence as in what Guy Davenport terms the 'contemporaneity' of two discontemporaneous minds, a constant affinity in thought, feeling, temperament, and interest. Whether their concern was Nature or Culture, art or literature, politics or economics, science or history, Ruskin and Pound held similar values, examined the same artefacts and issues, and often reached the same conclusions. The Anglo-Saxon world knows few more notable or savage critics of modern civilization, the break-up of community, the deterioration of the arts, and the money economy in its effects on every aspect of life.